The impact of e-commerce platforms' live-streaming features on Malaysian young adults' purchasing behavior - Yeong, Shu Wee (2023)
Livestream shopping is an act of purchasing products through social media and e-commerce platforms' broadcasting abilities. Live-streaming can boost a product’s exposure by allowing the owner to showcase the product to the audience directly. This research is to study the impact of livestream e-commerce platforms on youth's purchasing behavior by using the StimulusOrganism-Response (SOR) Theory. This study aims to determine the various "stimulus" and "organism" factors linked to livestream shopping in e-commerce platforms and to examine how "stimulus" and "organism" factors respectively affect consumer purchasing behavior (i.e.,response) among the youth aged from 15 to 30 in Klang Valley. The methodology of this study is a quantitative research approach, the demographic will be the youth from Klang Valley aged 15 and 30. Findings show that the visuality of the livestream e-commerce platform, the expertise of the broadcaster, and the product price significantly affected the purchasing behavior; while the viewers’ emotional and cognitive states positively affected the purchasing behavior of viewers. The study's importance involves giving the marketing industry a new view of how the youth behave while making purchases. It also serves as inspiration for social media developers looking to enhance the functionality of their programs with new features.